(untitled)
The single 2 dilation orthogonal wavelet multipliers in one dimensional case and single A-dilation (where A is any expansive matrix with integer entries and |detA|=2) wavelet multipliers in high dimensional case were completely characterized by the Wutam Consortium (1998) and Z. Y. Li, et al. (2010). But there exist no more results on orthogonal multivariate wavelet matrix multipliers corresponding integer expansive dilation matrix with the absolute value of determinant not 2 in L^2(R^2). In this paper, we choose 2I_2=(arraycc2 & 0 0 & 2array) as the dilation matrix and consider the 2I_2-dilation orthogonal multivariate waveletΨ={ψ_1,ψ_2,ψ_3}, (which is called a dyadic bivariate wavelet) multipliers. We call the 3× 3 matrix-valued function A(s)=[f_i,j(s)]_3× 3, where f_i,j are measurable functions, a dyadic bivariate matrix Fourier wavelet multiplier if the inverse Fourier transform of A(s)(ψ_1 (s),ψ_2 (s),ψ_3 (s))^=(g_1(s),g_2(s),g_3(s))^ is a dyadic bivariate wavelet whenever (ψ_1,ψ_2,ψ_3) is any dyadic bivariate wavelet. We give some conditions for dyadic matrix bivariate wavelet multipliers. The results extended that of Z. Y. Li and X. L. Shi (2011). As an application, we construct some useful dyadic bivariate wavelets by using dyadic Fourier matrix wavelet multipliers and use them to image denoising. , number=3, journal=Analysis in Theory and Applications, year=2017, month=July, pages=221–235